A novel anti-cancer effect of atelocollagen-conjugated miR-520d-5p on pancreatic cancer cells in vitro and in a mouse xenograft model. Issue 2 (2019) - Ishihara, Yoshitaka; Miura, Yugo; Miura, Norimasa; Miura, Keigo
No abstract available